The digital nudge in social security administration. (July 2016) - Gregor, Shirley; Lee‐Archer, Brian
Abstract: The concept of nudge theory, from the fields of behavioural science, political theory and behavioural economics, has sparked government initiatives yielding significant public value. A nudge is a method for predictably altering behaviour without restricting consumer choice options or significantly changing incentives. Nudges work by leveraging default human behaviour such as the tendency to take the path of least resistance when exercising choice. Government agencies have run many successful trials with simple textual nudges designed to positively influence behaviours such as tax compliance, voter registration and student attrition. This article develops the concept of the digital nudge in social security administration. The digital nudge leverages predictive analytics technology within a digital government framework to support a social investment policy approach. Based on a literature review of nudges within a digital government context, the article identifies examples of innovation within social security administration where nudges are contributing to better social outcomes. At the same time, concerns regarding ethics and privacy are identified as nudges are applied at the individual rather than the population level. The use of data and personal information to drive the nudge process has to be managed in such a way that individual rights are protected. This requirement has to be reconciled with the broader interests of society in achieving affordable outcomes, the parameters of which are determined through the political process.